ANATOMICAL AND CLINICAL JUSTIFICATION OF THE MODIFICATION OF MANDIBULAR ANESTHESIA IN THE BACK LOW BLOCK TECHNIQUE - Anisimov, M.V.; Anisimova, L.V.; Svitlychna, O.M.; Shnaider, S.A.; Mirchuk, B.M.; Baleha, M.I.; Zombor, K.V. (World of Medicine and Biology, 2024)
The study was dedicated to the improvement of the safety and effectiveness of conduction anesthesia on the mandible using an alternative method of mandibular anesthesia with appropriate anatomical justification and further testing of its clinical effectiveness. The anthropometric parameters of 91 dry anatomical preparations of the adult mandible were studied. Clinical observations were conducted in 440 patients aged 18 to 65 years. A total of 220 anesthetizations were performed using the traditional Inferior Alveolar Block technique and 220 anesthetizations using the Back Low Block technique for the treatment of caries and its complications. According to the results of a comparative evaluation of mandibular anesthesia using the traditional and the proposed methods with the use of standard anesthetic, a greater effectiveness of anesthesia in the Back Low Block technique was proved, as evidenced by an increase in the index of local anesthesia.